2019
DOI: 10.1039/c8cc08081j
|View full text |Cite
|
Sign up to set email alerts
|

Rapid assembly of cyclopentene spiroisoindolinones via a rhodium-catalysed redox-neutral cascade reaction

Abstract: A rhodium-catalysed redox-neutral cascade reaction starting from benzamides and cyclopropenones for the rapid assembly of cyclopentene spiroisoindolinones has been developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(23 citation statements)
references
References 58 publications
1
22
0
Order By: Relevance
“…Yuan et al [52] reported ar edox-neutral Rh III catalyzed double CÀHb ond functionalization cascade to produce 3-spiros ubstituted isoindolinones from 2,3-diarylcyclopropenones and benzamide derivatives (Scheme 15). In this manner, two new CÀC bonds and one new CÀNb ond were formed with the indene substituent at C3 positiono ft he isoindolinone skeleton.…”
Section: Rh-catalyzed Olefination/alkylation-cyclizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Yuan et al [52] reported ar edox-neutral Rh III catalyzed double CÀHb ond functionalization cascade to produce 3-spiros ubstituted isoindolinones from 2,3-diarylcyclopropenones and benzamide derivatives (Scheme 15). In this manner, two new CÀC bonds and one new CÀNb ond were formed with the indene substituent at C3 positiono ft he isoindolinone skeleton.…”
Section: Rh-catalyzed Olefination/alkylation-cyclizationmentioning
confidence: 99%
“…Yuan et al [52] . reported a redox‐neutral Rh III catalyzed double C−H bond functionalization cascade to produce 3‐spiro substituted isoindolinones from 2,3‐diarylcyclopropenones and benzamide derivatives (Scheme 15).…”
Section: C−h Functionalization: Annulation/cyclizationmentioning
confidence: 99%
“…Similar to C−H bond alkenylations (vide supra), the C−H bond activation step likely involved formation of a five‐membered metallacycle . This intramolecular cascade approach was later extended to different coupling partners (benzaldehydes, allylic alcohols, alkynes, diphenylcyclopropenone) leading to complex structures such as 3‐hydroxyisoindolin‐1‐ones, isoindolinones, cis ‐3,4‐dihydroisoquinolinones, and spiroisoindolinones (Scheme ) . Importantly, these examples show that the site‐selectivity of the catalysis is favored also because they lead to thermodynamically affordable five‐membered rings.…”
Section: C−c Bond‐forming Reactionsmentioning
confidence: 99%
“…β-Thiocyanate alkenyl esters represent highly valuable multifunctional compounds because both alkenyl ester and alkenyl thiocyanate moieties are broadly utilized in various fields such as organic synthesis, pharmacy, and material science. Directly converting propargylic carboxylates into β-thiocyanate alkenyl esters through multicomponent reaction represents a highly attractive transformation in organic synthesis, given the easily available raw materials. Recently, our group developed a novel method to synthesize various β-thiocyanate alkenyl esters in the range of 11–14:1 Z/E ratios from propargylic carboxylates via Brønsted acidic ionic liquid-catalyzed hydrothiocyanation of propargylic carboxylates .…”
Section: Introductionmentioning
confidence: 99%